Natural occurring epialleles determine vitamin E accumulation in tomato fruits - Quadrana, Leandro Daniel (2014)
Vitamin E (VTE) content is a low heritability nutritional trait for which the genetic determinants are poorly understood. Here, we focus on a previously detected major tomato VTE quantitative trait loci (QTL; mQTL 9-2-6) and identify the causal gene as one encoding a 2-methyl-6-phytylquinol methyltransferase (namely VTE3(1)) that catalyses one of the final steps in the biosynthesis of γ 3- and α -tocopherols, which are the main forms of VTE. By reverse genetic approaches, expression analyses, siRNA profiling and DNA methylation assays, we demonstrate that mQTL9-2-6 is an expression QTL associated with differential methylation of a SINE retrotransposon located in the promoter region of VTE3(1). Promoter DNA methylation can be spontaneously reverted leading to different epialleles affecting VTE3(1) expression and VTE content in fruits. These findings indicate therefore that naturally occurring epialleles are responsible for regulation of a nutritionally important metabolic QTL and provide direct evidence of a role for epigenetics in the determination of agronomic traits.